4,6-Dibromo-2-[(E)-(4-{[(E)-3,5-dibromo-2-hydroxybenzylidene]amino}butyl)iminomethyl]phenol - Hadi Kargar (Acta Crystallographica Section E, 2012)
The asymmetric unit of the title compound, C18H16Br4N2O2, comprises half the molecule, which is located adjacent to an inversion centre at the mid-point of the central C—C bond of the butane-1,4-diamine segment. There are two intramolecular O—H...N hydrogen bonds making S(6) ring motifs. In the crystal, molecules are linked by pairs of weak C—H...Br interactions into chains along [101], which include R22(8) ring motifs. These chains are further linked by C—H...O hydrogen bonds, forming a three-dimensional network.